2013
DOI: 10.1111/hir.12026
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of references in PhD theses: a case study

Abstract: Background: Inaccurate references and citations cause confusion, distrust in the accuracy of a report, waste of time and unnecessary financial charges for libraries, information centres and researchers. Objectives: The aim of the study was to establish the accuracy of article references in PhD theses from the Tehran and Tabriz Universities of Medical Sciences and their compliance with the Vancouver style. Methods: We analysed 357 article references in the Tehran and 347 in the Tabriz. Six bibliographic element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Although not much difference was seen in terms of the number of layout and formatting errors observed in graduate theses, this study establishes that thesis scrutiny has had a positive impact on the quality of graduate theses. Before the implementation of thesis consultation, the citation errors observed in the theses submitted in 2009 compare favorably with the findings of Azadeh and Vaez (2013) in which very few of the theses were completed according to the required citation style. However, after thesis consultation was implemented, there was a steady decline in the number of reference errors seen in graduate theses for 2011 and 2014.…”
Section: Findings and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Although not much difference was seen in terms of the number of layout and formatting errors observed in graduate theses, this study establishes that thesis scrutiny has had a positive impact on the quality of graduate theses. Before the implementation of thesis consultation, the citation errors observed in the theses submitted in 2009 compare favorably with the findings of Azadeh and Vaez (2013) in which very few of the theses were completed according to the required citation style. However, after thesis consultation was implemented, there was a steady decline in the number of reference errors seen in graduate theses for 2011 and 2014.…”
Section: Findings and Discussionsupporting
confidence: 55%
“…A number of authors examine the accuracy of citations. In a study by Azadeh and Vaez (2013), the authors found that references in the PhD theses that they looked at were inaccurate. Of the 357 articles that were checked, they found that only 9.8 per cent were completed in accordance with the required citation style.…”
Section: Thesis Scrutiny: Citation and Referencingmentioning
confidence: 99%
“…Thirty four references (9.8%) out of 357 in the Tehran were compiled according to the Vancouver referencing style. According to Azadeh and Vaez (2013), "accuracy of referencing did not differ significantly between the two groups, but compliance with the Vancouver style was significantly better in the Tehran" 51 (p. 232).…”
Section: Reference Accuracy In Doctoral Thesesmentioning
confidence: 93%
“…Wrong citations mistrust in the accuracy of a research, create dilemma, wastage of time and unwanted "financial charges for information centres, libraries and researchers" 51 (Azadeh & Vaez, 2013). The main objective of Azadeh and Vaez"s (2013) research was to determine the reference accuracy of journal articles in doctoral theses in Farsi.…”
Section: Reference Accuracy In Doctoral Thesesmentioning
confidence: 99%
“…For example, the results of Harinarayana's study on the citation accuracy of psychology dissertations showed that 77 per cent of citations contained errors 17 . Azadeh and Vaez showed that there are citation errors in more than half of the doctoral dissertations reviewed, emphasizing educating students in this area 18 .…”
Section: Literature Reviewmentioning
confidence: 99%